Pemberdayaan Pesantren Darul Ulum Pakkatto untuk Kemandirian Pangan melalui Pelatihan dan Pendampingan Budidaya Ikan Nila Bioflok: Pengabdian - Rina, Rina; Andi, Hendra Syam; Bando, Nurjannah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The purpose of this community service program is to increase the food independence of the Darul Ulum Pakkatto Islamic Boarding School in Gowa Regency by providing training and assistance on how to cultivate tilapia with a biofloc system. The pesantren has a number of students ±225 people currently depends entirely on the supply of fish from outside, with a consumption of ±30 kg per week. This creates an uncertain cost burden and supply risk. Despite this, the pesantren has an open land area of 110,000 square meters with two concrete pools that have not been properly utilized. This program is carried out in three stages: (1) Field survey to determine the needs and potential of cultivation; (2) Design of biofloc cultivation media, including pond cleaning, construction of new ponds, installation of aeration, and provision of supporting facilities; and (3) Technical training and assistance, including water quality management, seed distribution, feeding, and fish health monitoring. The results of the activity showed that the participants gained the knowledge and skills needed to carry out tilapia cultivation independently. This program can reduce pesantren dependence on food sources, reduce operating costs, and provide students with business opportunities. Biofloc technology has proven to be successful as a food independence solution based on pesantren that can be applied elsewhere.